Adolescents’ physical activity is associated with previous and current physical activity practice by their parents - Christofaro, Diego Giulliano Destro [UNESP]; Andersen, Lars Bo; Andrade, Selma Maffei de; Barros, Mauro Virgílio Gomes de; Saraiva, Bruna Thamyres Ciccotti [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Ritti-Dias, Raphael Mendes (Elsevier, 2018)
Objective The purpose of this study was to determine whether parents’ current and previous physical activity practice is associated with adolescents’ physical activity. Methods The sample was composed of 1231 adolescents (14–17 years), and 1202 mothers and 871 fathers were interviewed. Weight and height of the adolescents were measured. Self-reported parents’ weight and height were obtained. The current and previous physical activity levels (Baecke's questionnaire) of parents (during childhood and adolescence) and adolescents’ physical activity levels were obtained using a questionnaire. The magnitude of the associations between parent and adolescent physical activity levels was determined by binary logistic regression (adjusted by sex, age, and socioeconomic level of adolescents and education level of parents). Results The current physical activity practice by parents was associated with adolescents’ physical activity (p < 0.001). The physical activities reported by parents in their childhood and adolescence were also associated with higher physical activity levels among adolescents. Adolescents whose parents were both physically active in the past and present were six times (OR = 6.67 [CI = 1.94–22.79]) more likely to be physically active compared to adolescents with no parents who were physically active in the past. Conclusions The current and previous physical activities of parents were associated with higher levels of physical activity in adolescents, even after controlling for confounding factors.
A atividade física de adolescentes está associada à prática de atividade física anterior e atual por seus pais
Keywords: Adolescents; Current physical activity; Modeling; Parents; Previous physical activity; Social support